FUZZY IDEALS OF IMPLICATION GROUPOIDS - Bandaru, Ravi Kumar; Shum, K.P.; Rafi, N. (Italian Journal of Pure and Applied Mathematics, 2015)
In this paper, we introduce the concept of fuzzy ideals in implication groupoids and investigate its properties.